2020 IEEE Conference on Games (CoG) 2020
DOI: 10.1109/cog47356.2020.9231752
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for embodied cognition in immersive virtual environments using a second language learning environment

Abstract: Immersive virtual environments (IVEs) are increasingly being explored as potential educational tools. However, it is unclear which aspects of IVEs contribute to learning, including hardware modalities and learner responses (e.g. motivation, usability, cognitive load and presence). One IVE hardware modality particularly backed by theory is embodied controls, with their potential for leveraging embodied cognition for enhanced learning outcomes. This paper explores if embodied controls can be leveraged to enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
3
4
0
Order By: Relevance
“…We did not find a significant difference in learning retention after one week between the two encoding conditions, although the action condition showed a higher, non-significant, mean learning gain. This is similar to results in previous work [38]. There are three potential explanations for the difference in significance between the immediate and one-week later tests: (1) the drop in participants (from 48 to 35), as many did not complete the one-week later test, reduced the sensitivity of the test; (2) the difference in learning between the conditions is reduced but not eliminated, reducing the sensitivity of the test; (3) learning gain differences between action and gesture only occur immediately, and longer-term learning is similar between conditions.…”
Section: Missing Retention Similar Response Timessupporting
confidence: 93%
See 1 more Smart Citation
“…We did not find a significant difference in learning retention after one week between the two encoding conditions, although the action condition showed a higher, non-significant, mean learning gain. This is similar to results in previous work [38]. There are three potential explanations for the difference in significance between the immediate and one-week later tests: (1) the drop in participants (from 48 to 35), as many did not complete the one-week later test, reduced the sensitivity of the test; (2) the difference in learning between the conditions is reduced but not eliminated, reducing the sensitivity of the test; (3) learning gain differences between action and gesture only occur immediately, and longer-term learning is similar between conditions.…”
Section: Missing Retention Similar Response Timessupporting
confidence: 93%
“…Vasquez found that verbs were remembered better if encoded by performing congruent actions than if learning using traditional text-based memorisation [56]. Ratcliffe found that a combination of verbs and nouns were remembered better if they were encoded by performing actions with objects in IVR, than if there were those actions were not performed but the objects were still present [38]. Fuhrman found improved learning rates for nouns that were learned when using a relevant sensorimotor activity compared to an irrelevant sensorimotor activity or no sensorimotor activity [7]; while Macedonia found similar [25].…”
Section: Sensorimotor Ivr Benefits; Action and Gesture Distinctions?mentioning
confidence: 99%
“…Their results showed higher engagement scores and greater learning for the more embodied conditions. Ratcliffe and Tokarchuk (2020) found similar results in their study on the impact of embodied controls on language learning outcomes in an immersive VR environment. The study compared the learning outcomes of participants who used embodied controls with those who used non‐embodied controls.…”
Section: Movement and Embodied Cognition In Vrsupporting
confidence: 62%
“…To disentangle the above-mentioned issues, studies focusing on the embodied effects in L2 processing have been conducted. The results indicated that, as in L1 processing, the sensorimotor system is also involved in L2 processing, although some differences were found in terms of degree or time course (De Grauwe et al, 2014;Dudschig et al, 2014;Vukovic and Williams, 2014;Foroni, 2015;Buccino et al, 2017;Ratcliffe and Tokarchuk, 2020).…”
Section: Introductionmentioning
confidence: 91%